Safety profile in pregnant rats of a natural antidiabetic agent extracted from Mormodka charantia - Fernandopulle, B.M.R.; Ratnasooriya, W.D. (My University, 1999)
We have examined the effects of an unripe fruit extract of Mormodica charantia Linn, on pregnancy outcome of rats when given during early- (days 1-7), mid- (days 8-16) and late- (days 15-21) gestation. The extract was administered orally in two different concentrations (1 ml/100 g/day or 2 ml/100 g/day). Several parameters of reproduction and neonatal development were detennined and computed. The extract did not have deleterious effects on pregnancy outcome during early pregnancy (in terms of vaginal bleeding and pre- and post-implantation losses), late pregnancy (in terms of vaginal bleeding, number of pups bom and day of partus) or neonatal development (in terms of body weight, time taken for the appearance of fur and opening eyes of pups). In contrast, during mid-pregnancy, the extract induced vaginal bleeding, resorption of fetuses, post-implantation losses, small for dates fetuses and retardation of fetal growth. However, the number of uterine implants remained unin:q>aired. Further, the extract had no effect on the duration or stage of the oestrous cycle in normally cycling rats. The fetal growth retardation is likely to have been mediated via the hypoglycaemic activity of the extract. We conclude that M. charantia should not be recommended as a natural antidiabetic drug in diabetes complicating pregnancy and that its heavy consumption is best avoided in normal pregnancy (especially during midgestation).